Obstetric Fistula in the Developing World: An Agonising Tragedy - Dangal, G; Thapa, K; Yangzom, K; Karki, A (Nepal Journal of Obstetrics and Gynaecology, 2014)
Obstetric fistulae is the most tragic of preventable childbirth complications in the developing world, as affected women are often abandoned by their husbands and family, and forced to live in shame. They occur almost entirely in the developing world and their incidence is poorly studied. Their management requires accurate diagnosis, sufficient pre-operative work-up, fine surgery following standard surgical repair steps and principles by skilled surgeons, specialised post-op care, and follow-up. As obstetric fistula is a serious preventable public health issue in developing countries, national and international organizations should launch a campaign to end fistula by increasing the resources and skilled staff available locally to treat obstetric fistula for improving the lives of women currently living with this condition. Moreover, effective preventive strategies for obstetric fistula such as better education to women and provision of improved obstetric care and searching for the best approaches to both prevention and treatment should be the priority. The materials published in PubMed, Lancet, Medline, WHO and Google Scholar web pages from 1990 to 2013 have been utilized to prepare this paper. Nepal Journal of Obstetrics and Gynaecology / Vol 8 / No. 2 / Issue 16 / July-Dec, 2013 / 5-15 DOI: http://dx.doi.org/10.3126/njog.v8i2.9759